심볼릭 수행 방법을 이용한 철도 소프트웨어 코드분석 도구제안 - 조현정(Hyun-Jeong Jo); 황종규(Jong-Gyu Hwang); 신덕호(Duck-Ho Shin) (전기학회 논문지 P권, 65(4), 2016)
The railway system is being converted to the computer system from the existing mechanical device, and the dependency on software is being increased rapidly. Though the size and degree of complexity of software for railway system are slower than the development speed of hardware, it is expected that the size will be grown bigger gradually and the degree of complexity will be increased also. Accordingly, the validation of reliability and safety of embedded software for railway system was started to become influential as the important issue. Accordingly, various software test and validation activities are highly recommended in the international standards related railway software. In this paper, we presented a software coding analysis tool using symbolic execution for railway system, and presented its result of implementation.